Description of spectra and derivations of Wiener type algebras of functions generated by $(p,q)$-polynomials on Banach spaces - Vasylyshyn, T.V. (Carpathian Mathematical Publications, 2012)
It is described a spectra of Wiener type algebras of functions generated by $(p,q)$-polynomials on Banach spaces. Derivations on these algebras introduced and investigated.